1996
DOI: 10.1097/00005392-199609000-00026
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Epitectin (MUC-1 Glycoprotein) in the Menstrual Cycle and Interstitial Cystitis

Abstract: Decreased mean urinary epitectin levels may reflect a cause (epithelial mucin deficiency) or a consequence of interstitial cystitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
1
0
1
Order By: Relevance
“…Speci c glycoconjugates and carbohydrate-binding proteins, i.e., lectins, play important roles in animal development, physiology, and various pathological states. We are investigating the role of bladder epithelial glycoconjugates in bladder disorders such as interstitial cystitis (1)(2)(3). In continuation of these studies, histochemical examination of rabbit and human bladder sections revealed strong calcium-independent binding of b -Dgalactose neoglycoconjugates (4).…”
Section: Introductionmentioning
confidence: 99%
“…Speci c glycoconjugates and carbohydrate-binding proteins, i.e., lectins, play important roles in animal development, physiology, and various pathological states. We are investigating the role of bladder epithelial glycoconjugates in bladder disorders such as interstitial cystitis (1)(2)(3). In continuation of these studies, histochemical examination of rabbit and human bladder sections revealed strong calcium-independent binding of b -Dgalactose neoglycoconjugates (4).…”
Section: Introductionmentioning
confidence: 99%
“…Concernant les métabolites urinaires des glycosaminoglycanes, il n'existe pas de consensus quant au taux d'acide hyaluronique urinaire retrouvé dans les cystites interstitielles, diminué pour les uns [26], augmenté pour les autres [27]. La variabilité de ces résultats rend nécessaire des études de corrélation entre les biopsies de vessie et le taux urinaire de GAG retrouvé.…”
Section: Marqueurs Urinairesunclassified